2009
DOI: 10.1051/agro:2008070
|View full text |Cite
|
Sign up to set email alerts
|

A 25-year record of carbon sequestration and soil properties in intensive agriculture

Abstract: -As a major carbon pool on earth, soil organic carbon may act either as a sink or a source of atmospheric CO 2 , a greenhouse gas. Soil organic carbon is also impacting fertility, and, in turn, crop yields. However, knowledge of the impact of cropping techniques on the long-term behavior of soil carbon is scarce. Several studies have shown that continuous cropping decreases soil organic carbon stocks, rapidly in the initial years then at a slower rate, approaching a new equilibrium after 30 to 50 years. For in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 23 publications
(18 reference statements)
2
19
1
Order By: Relevance
“…4) after the conversion. The average soil carbon sequestration rate following the conversion from CVC to PGVC is about six times greater than that of the conversion from conventional cropland to no-till (in China, 0.16e0.39 Mg C ha À1 yr À1 , Lu et al, 2009 and in USA, 0.34 Mg C ha À1 yr À1 , West and Marland, 2002;respectively), and about 3.5-fold greater than that of rice-wheat intensive agriculture (0.62 Mg C ha À1 yr À1 , Benbi and Brar, 2009). This may be primarily attributed to the higher organic fertilizer carbon inputs (1.3-to 3.0-fold that of CVC, Fig.…”
Section: Carbon Flux Change Following the Conversion From Cvc To Pgvcmentioning
confidence: 96%
See 1 more Smart Citation
“…4) after the conversion. The average soil carbon sequestration rate following the conversion from CVC to PGVC is about six times greater than that of the conversion from conventional cropland to no-till (in China, 0.16e0.39 Mg C ha À1 yr À1 , Lu et al, 2009 and in USA, 0.34 Mg C ha À1 yr À1 , West and Marland, 2002;respectively), and about 3.5-fold greater than that of rice-wheat intensive agriculture (0.62 Mg C ha À1 yr À1 , Benbi and Brar, 2009). This may be primarily attributed to the higher organic fertilizer carbon inputs (1.3-to 3.0-fold that of CVC, Fig.…”
Section: Carbon Flux Change Following the Conversion From Cvc To Pgvcmentioning
confidence: 96%
“…4). This is attributed to greater carbon input through root exudates and organic fertilizer input in the colder regions (Benbi and Brar, 2009;Qiu et al, 2010;Wang et al, 2011). The PGVC in colder regions received more organic fertilizers than that in warmer regions because of a greater economic return from PGVC in colder regions.…”
Section: Mechanisms For Regional Variations In Net Carbon Fluxesmentioning
confidence: 99%
“…Furthermore, SCS is natural, cost-effective and environmental friendly process and it is also helpful to achieve food security by improving soil fertility (Lal 2004a). Literature provides ample evidence on the mechanisms and processes of C-sequestration especially in soils (Kögel-Knabner et al 2008;Lal 2009;Benbi and Brar 2009;Sigua and Coleman 2009;Jones et al 2009;Morra et al 2010). However, the present review was aimed to critically analyze SCS as a carbon mitigation option and its role in agricultural productivity, wasteland reclamation, increment in biological diversity and its future perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of stagnating or declining rice and wheat yields in the IGP (Ladha et al 2003), which have presumably been related to declining soil organic matter (SOM) content and decreased soil fertility (Bhandari et al 2002;Regmi et al 2002). However, temporal analysis of 25-years data on organic C content of the regional soils showed that the stagnating productivity was not related to SOC (Benbi and Brar 2009). So far there is no information available on the quality of SOM under ricewheat system in comparison to other agroecosystems.…”
Section: Introductionmentioning
confidence: 99%